Examining The Relationship Between Dyadic Adjustment And Psychological Resilience Between Hemodialysis Patients And Their Spouses. - TANRIVERDİ, Ömer and IŞIL, Özlem (Göbeklitepe Medical Science Journal, 2022)
In patients receiving hemodialysis treatment, the physical, mental and psychosocial problems that occur in this process can negatively affect all areas of the individual’s life. Healthy communication between couples, harmony between spouses increases compliance and resilience with chronic disease. This relational descriptive study was conducted with 128 hemodialysis patients hospitalized in the dialysis service of 3 public hospitals in the city center of Mardin. The data were collected using a Patient Information Form, the Revised Dyadic Adjustment Scale (RDAS), the Psychological Resilience Scale for Adults (PRSA), number, percentage, mean independent groups t test, One-Way ANOVA, and Pearson Correlation Analysis were used. Patients mean age was 44.74 ± 9.07 and 64.1% were male, 27.3% were primary school graduates, 89.8% did not work, 39.1% were on dialysis more than 6 years, 44.5% were married longer than 21 years. The mean PRSA score was 104.40 ± 22.16, and the RDAS was 48.10 ± 14.57. A strong positive correlation was found between psychological resilience and the dyadic adjustment between couples.